Pengembangan Jiwa Kewirausahaan Melalui Unit Produksi “Siklus” dengan Strategi Pembelajaran Teaching Factory Menuju Sekolah Pencetak Wirausaha - Agus Triyana; Cicilia Wahyu Wening P; Indriyani Voluntri Aziz (Jurnal Pendidikan Dasar, 2022)
The writing aims to describe the planning, process, and results of implementing thedevelopment of an entrepreneurial spirit through a superior product "cycle" with a teachingfactory learning strategy towards an entrepreneurial school at SMKN 7 Purworejo Inaccordance with the competency standards of graduates at SMK, namely producing graduateswho are ready to become workers or entrepreneurship and continue higher education inaccordance with their vocational skills, it encourages authors to improve the entrepreneurialspirit at SMK N 7 Purworejo to prepare graduates or skilled workers to shape studentstowards human resources. Human (HR) quality so that it can create jobs and reduce thenumber of unemployed. The "SIKLUS" Production Unit as one of the production units that hasbeen running at SMK N 7 Purworejo which is implemented using a teaching factory learningstrategy in the competency of Fashion Design is a means of developing entrepreneurship forschool residents. The product "SIKLUS" has become the flagship product of SMK N 7Purworejo which has also become the mainstay of the Purworejo Regency Industry Office tobecome an example of useful work to improve the economy of the people in Purworejo.